Observasi Unsur Cuaca Terhadap Morfologi Buah Tanaman Kelapa Sawit (Elaeis Guineensis Jacq) Di Dataran Tinggi - Eros Anggara Lubis; Hari Gunawan (JURNAL AGRICA, 2026)
This study aims to conduct in-depth observations on how the morphological characteristics of oil palm (Elaeis guineensis Jacq) fruit growing in highland ecosystems are influenced by weather factors. This study was conducted at the Bah Birung Ulu Plantation in North Sumatra, at an altitude of between 660 and 1,100 meters above sea level (masl). This study used an observational descriptive approach by conducting direct observations of three productive sample trees in Afdeling 3. Weather elements (daily temperature, rainfall, and humidity) and fruit morphology (mesocarp, endocarp, and kernel thickness, as well as fruit set). The results showed that the average temperature at the location ranged between 20.4°C and 22.7°C, which is far below the optimal standard for oil palm growth, which is 24-28°C. With high air humidity of 83–89% and annual rainfall of 3,591 mm, the physical dimensions of the fruit were less than optimal. The measurement results showed that the average mesocarp thickness was only 13.56 mm to 14.76 mm, indicating that low temperatures in the highlands slow down fruit flesh metabolism and oil biosynthesis processes. However, a fruit set value of 81% was found in all sample trees, indicating that the pollination process was still running well above the 75% threshold.[li1.1][h1.2] This study found that extreme low temperatures and high humidity physically limit fruit morphological development but do not significantly reduce the pollination success of bunches.